Kitty in the underworld eaudiobook - Vaughn, Carrie (Kitty Norville, 2013)
As Denver adjusts to a new master vampire, Kitty gets word of an intruder in the Denver werewolf pack's territory, and she investigates the challenge to her authority. She follows the scent of the lycanthrope through the mountains where she is lured into a trap, tranquilized, and captured. When she wakes up, she finds herself in a defunct silver mine: the perfect cage for a werewolf. Her captors are a mysterious cult seeking to induct Kitty into their ranks in a ritual they hope will put an end to Dux Bellorum. Though skeptical of their power, even Kitty finds herself struggling to resist joining their cause. Whatever she decides, they expect Kitty to join them in their plot . . . willingly or otherwise.